Homeopathic Management of Breech Presentation: An Evidence-Based Case Report - Manasa, P.S.K.P. (Homœopathic Links, 2025)
The fetus continuously moves within its swimming pool, “the amniotic fluid,” until approximately 36 weeks of gestation, when the head typically engages into the maternal pelvis. Breech presentation, where the buttocks enter the pelvis first, is associated with significant complications for both the mother and the fetus. While several methods exist to convert breech presentation to cephalic presentation, homeopathy is considered a potentially painless and safer alternative. This case report describes the case of a 30-year-old woman at near term with a breech presentation diagnosed by ultrasound. Opting for homeopathy, over external cephalic version (ECV), she was prescribed Pulsatilla 200c, once daily, for 3 days. Remarkably, a follow-up ultrasound revealed a successful conversion to cephalic presentation. The fetus remained in this position until a normal, uncomplicated vaginal delivery at 40 weeks of gestation. The primal/perinatal period is critical for maternal and fetal health. Medications administered to expectant mothers during this time can prevent or treat various conditions, including malpresentations and abortions.
Keywords: breech; homeopathy; malpresentation; pulsatilla; turn breech; version